Thermal Stability of Clay's Galleries in Polypropylene - Clay (montmorillonite) Nanocomposites using Polypropylene-gMaleic Anhydride as Compatibilizer - Astutiningsih, Sotya; Kinasih, Pandu Lanang; Wibowo, Arief Cahyo (UI Scholars Hub, 2009)
Thermal Stability of Clay's Galleries in Polypropylene - Clay (montmorillonite) Nanocomposites using Polypropylene-g- Maleic Anhydride as Compatibilizer. Superior properties of food packaging can be achieved using nanocomposite technology. However, fabrication of this materials are complex and expensive. Long term objectives of this research is the synthesis of low cost polypropylene clay nanocomposites (PPCN) via a short-cut method known as ‘cascade engineering’. Cascade engineering principle in PPCN fabrication is performed by using compatibilizer (to enable the mixing of PP and clay) masterbatch, and PPCN in one pot process using melt mixer. This paper present the experimental results using small-angle x-ray diffraction (XRD) on the thermal stability of the PPCN. Results from the XRD analysis showed that the clay was intercalated, however no significant changes were observed as a result of variation in mixing time. XRD patterns of the annealed PPCN showed reduction of MMT’s gallery (deintercalation) These phenomenon was probably caused by insufficient bonding and lack of compatibility between PP-g-MA and MMT.